2007
DOI: 10.1007/s00192-007-0322-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence in Korean women:an epidemiologic survey

Abstract: The purpose of this study was to evaluate the prevalence of urinary incontinence (UI) in a Korean national community sample of female adults aged 30-79 years. During April 2003, a national Korea telephone survey using quota sampling methods was conducted. The clinically validated computer-assisted telephone interview approach was used in the survey. Of the 1,500 subjects contacted, 1,303 were successfully interviewed (response rate 86.9%). Overall, UI was reported by 40.8%, and 22.9, 3.1, and 14.9% reported pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Prevalence rates vary according to study populations, methods of investigation, and the operative definition being used. In recent studies, 20-55% of community-dwelling women report involuntary leakage of urine [1][2][3][4][5][6][7]. It is also well-known that UI has an adverse effect on patients' daily lives and could become an important barrier to normal function in the social, family, or work environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates vary according to study populations, methods of investigation, and the operative definition being used. In recent studies, 20-55% of community-dwelling women report involuntary leakage of urine [1][2][3][4][5][6][7]. It is also well-known that UI has an adverse effect on patients' daily lives and could become an important barrier to normal function in the social, family, or work environment [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, until recently, a consensus has not been available concerning the definition of OAB. Earlier studies reported that OAB was characterized by the prevalence of urinary incontinence and nocturia in a specific age group [19, 20], and OAB was investigated in the presence of urgency without verified survey items [2, 16]. Although a population-based study was conducted in Korean men, the study was conducted by telephone survey, with a response proportion as low as approximately 22.1% [16].…”
Section: Introductionmentioning
confidence: 99%
“…LUTS are recognized as a common condition in men aged ≥40 years, and its prevalence increases with age [2,3,4]. Several epidemiologic studies have focused on LUTS in Korea [5,6,7,8,9,10], as well as in other Asian [11,12,13] and Western countries [14,15,16,17,18]. However, the true prevalence of LUTS is difficult to determine because most studies have examined specific symptoms related to benign prostatic hyperplasia [8,13], urinary incontinence [7,9,10,14], or overactive bladder [5,6,12,15,17,18] rather than LUTS in general.…”
Section: Introductionmentioning
confidence: 99%